Parallel phage resistance - virulence trade - offs during clinical phage therapy and in vitro. Issue 5 (27th May 2022) - Castledine, Meaghan; Padfield, Daniel; Sierocinski, Pawel; Pascual, Jesica Soria; Hughes, Adam; Mäkinen, Lotta; Friman, Ville-Petri; Pirnay, Jean-Paul; Vos, Daniel De; Buckling, Angus
Abstract : With rising antibiotic resistance, modern medicine needs new approaches for tackling bacterial infections. Phage therapy uses the viruses of pathogenic bacteria to clear the infection. Unlike antibiotics, phage can evolve if bacteria become resistant to maintain or even increase their infectivity (coevolution). While laboratory studies can give insight into complex bacteria-phage interactions, whether they act as a true representation of phage therapy in patients is unknown. Here, we compared phage therapy in a patient to that of in vitro experiments. The patient had been admitted with aPseudomonas aeruginosainfection and was successfully treated with a phage cocktail. Bacteria were isolated before and during phage therapy, allowing us to follow bacteria-phage coevolution in the patient while doing experiments on the same clones in vitro. In vivo and in vitro, bacteria rapidly evolved resistance with little or no evidence of bacteria - phage coevolution. Although resistance mechanisms differed, parallel resistance - virulence trade-offs were found in vivo and in vitro. Therefore, phage resistance could increase treatment success and our results indicate to what extent bacteria - phage evolutionary dynamics can be predicted from in vitro experiments.